2020
DOI: 10.1021/acs.energyfuels.0c01381
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Nanoalumina and CNTs-Reinforced Microcapsules with n-Dodecane as a Phase Change Material for Cold Energy Storage

Abstract: A series of microencapsulated phase change materials (MEPCMs) containing nanoalumina-reinforced n-dodecane (C12) as core materials and modified carbon nanotubes (CNTs) reinforced melamine–formaldehyde (MF) resin as shell materials was synthesized successfully via in situ polymerization. The effects of CNTs and nanoalumina on the morphology/thermal performance of the MEPCMs were investigated by scanning electron microscopy (SEM), Fourier transform infrared (FT-IR), differential scanning calorimetry (DSC), laser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 43 publications
(62 reference statements)
0
6
0
Order By: Relevance
“…Microencapsulation methods can generally be divided into physical or chemical methods. At present, the most commonly used methods are spray drying, , sol–gel method, , complex coacervation, , interfacial polymerization, , in situ polymerization, , suspension polymerization, , microemulsion polymerization, and self-assembly method …”
Section: Methodsmentioning
confidence: 99%
“…Microencapsulation methods can generally be divided into physical or chemical methods. At present, the most commonly used methods are spray drying, , sol–gel method, , complex coacervation, , interfacial polymerization, , in situ polymerization, , suspension polymerization, , microemulsion polymerization, and self-assembly method …”
Section: Methodsmentioning
confidence: 99%
“…The latent heat decreased very little, and the performance of the material was stable after 100 cycles of experiments. Dong et al 107 prepared microcapsules based on C12 and added nanoalumina and CNTs to it. It was found that the addition of nanoparticles greatly increased the TC and reduced the degree of subcooling, but the addition of CNTs reduced the latent heat of the material.…”
Section: Role Of Additives and Comparativementioning
confidence: 99%
“…Q to =τ over is the instantaneous heat transfer rate, while Q to =ðτ over A cs Þ is the heat flux q av , q av =ðT s À T cs Þ is the equivalent heat transfer coefficient. The equivalent heat transfer coefficient is defined as the cold energy charging coefficient, as shown in Equation (18).…”
Section: Cold Energy Charging Coefficientmentioning
confidence: 99%
“…[16,17] The microscale research object is called a microcapsule. [18,19] 4) The external convective heat transfer coefficient is increased by increasing the flow rate of HTF. [20] These measures strengthen the heat transfer capacity…”
Section: Introductionmentioning
confidence: 99%